Percutaneous Trans-Carotid Puncture for Mechanical Thrombectomy in Acute Ischemic Stroke Patients is Safe and Effective: A Large, Single-Center Case Series. (1st September 2019) - Cord, Branden J; Wang, Anson; Chouairi, Fouad; Koo, Andrew; Porto, Carl; Silverman, Andrew; Kodali, Sreeja; Strander, Sumita; Falcone, Guido; Sheth, Kevin; Hebert, Ryan M; Sansing, Lauren; et al.
Abstract: INTRODUCTION: Although endovascular thrombectomy is a highly effective treatment for patients with large-vessel occlusion stroke, the procedure can be prolonged, or even impossible, due to difficult vascular access. We hypothesized that patients undergoing percutaneous transcarotid puncture (PTCP) as an alternative approach would have improved functional outcome compared to patients where a transfemoral approach was precluded. METHODS: For PTCP, a 6F (5.5-cm) sheath was placed in the common carotid artery using an ultrasound-guided, micropuncture technique. Mechanical thrombectomy (MT) was performed using a stent retriever with adjunctive contact aspiration. We compared patients with unsuccessful MT due to transfemoral access failure with patients who were treated using PTCP. Functional outcome was assessed using the modified Rankin scale (mRS) at 3-mo. Associations with outcome were analyzed using ordinal logistic regression, adjusted for age and admission NIHSS. RESULTS: PTCP was performed in 20 cases and carotid access was successfully obtained in 19/20 patients (1 abandoned due to inability to safely cannulate the artery). A total of 17 patients who were well matched for age, gender, and admission NIHSS served as historical controls. A total of 36 patients were included in the final analysis (82 yr [SD 11], 25 M, mean admission NIHSS 17). Successful reperfusion (TICI 2b-3) was achieved in 16/19 (84%), with 26% achieving good outcome (mRS 0-3) at 90 d compared to 6% of historical controls. In the shift analysis, PTCP was independently associated with lower (better) mRS scores at 3 mo (adjusted common OR 5.2, 95% CI 1.02-24.5, P = .048). PTCP cases also had smaller infarct volumes (median 11 vs 48 ml, P = .041) and greater reduction in NIHSS (−4 vs + 2.9, P = .034). A single patient suffered a fatal carotid blowout on post-MT day 4. CONCLUSION: PTCP for emergent MT is a safe and effective strategy that yields high recanalization rates, decreased infarct volumes and improved functional outcome among patients with transfemoral access failure.